2011
DOI: 10.1371/journal.pgen.1002436
|View full text |Cite|
|
Sign up to set email alerts
|

Interspecific Sex in Grass Smuts and the Genetic Diversity of Their Pheromone-Receptor System

Abstract: The grass smuts comprise a speciose group of biotrophic plant parasites, so-called Ustilaginaceae, which are specifically adapted to hosts of sweet grasses, the Poaceae family. Mating takes a central role in their life cycle, as it initiates parasitism by a morphological and physiological transition from saprobic yeast cells to pathogenic filaments. As in other fungi, sexual identity is determined by specific genomic regions encoding allelic variants of a pheromone-receptor (PR) system and heterodimerising tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 102 publications
6
59
0
4
Order By: Relevance
“…A somewhat parallel situation was observed in the distantly related red yeasts of the Sporidiobolales (class Microbotryomycetes, subphylum Pucciniomycotina) for which genomic regions around the P/R locus exhibited extensive rearrangements between complementary mating types of each species, while synteny was well conserved across species when the homologous regions of the same mating type were compared (41). A similar conclusion was reached by Kellner et al (6) when comparing the triallelic P/R loci of different smut species in the Ustilaginomycetes. These findings suggest that the MAT gene structure of each allele of the P/R loci in different species was fixed long before speciation occurred.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A somewhat parallel situation was observed in the distantly related red yeasts of the Sporidiobolales (class Microbotryomycetes, subphylum Pucciniomycotina) for which genomic regions around the P/R locus exhibited extensive rearrangements between complementary mating types of each species, while synteny was well conserved across species when the homologous regions of the same mating type were compared (41). A similar conclusion was reached by Kellner et al (6) when comparing the triallelic P/R loci of different smut species in the Ustilaginomycetes. These findings suggest that the MAT gene structure of each allele of the P/R loci in different species was fixed long before speciation occurred.…”
Section: Discussionsupporting
confidence: 66%
“…In the bipolar species, there are normally only two possible versions for the content of the single MAT locus, and hence only two mating types exist. Recent studies have suggested that the basidiomycete bipolar mating systems are evolutionarily derived from tetrapolar ancestral states (4)(5)(6).…”
mentioning
confidence: 99%
“…Second, within the same strain, pheromone precursor genes code for identical peptides, suggesting the presence of only one MAT specificity per strain. This organization contrasts, for example, with the triallelic P/R locus of several smut species in the Ustilaginales, in which two different MAT-specific pheromones are encoded at each P/R allele (Schirawski et al 2005;Kellner et al 2011). It also differs from other model species in the subphylum Agaricomycotina, such as Schizophyllum commune and C. cinerea, in that these species have evolved an enormous repertoire of pheromone/receptor alleles likely arising by duplication of an archetypal P/R locus, followed by rounds of recombination and diversification between alleles (Riquelme et al 2005).…”
mentioning
confidence: 93%
“…& Begerow AJ236155 (Piepenbring et al, 1999), Tolyposporium isolepidis EU246949 (Vánky & Lutz, 2008), Tolyposporium junci AF009876 (Begerow et al, 1997), Tolyposporium neillii EU246952 (Vánky & Lutz, 2008), Tolyposporium piluliforme AF009871 (as Heterotolyposporium piluliforme, Begerow et al, 1997), Ustanciosporium gigantosporum (Liro) M. Piepenbr. JN367325 (Kellner et al, 2011), Ustanciosporium standleyanum (Zundel) M. Piepenbr. JN367326 (Kellner et al, 2011), Ustilago affinis Ellis & Everh.…”
Section: Methodsmentioning
confidence: 99%
“…JN367325 (Kellner et al, 2011), Ustanciosporium standleyanum (Zundel) M. Piepenbr. JN367326 (Kellner et al, 2011), Ustilago affinis Ellis & Everh. AF133581 (Begerow et al, 2000), Ustilago echinata J. Schröt.…”
Section: Methodsunclassified